Neurocognitive deficits in clinical polymorphism of schizophrenia: typology, expression and syndromal overlaps - A. N. Kornetov; E. G. Kornetova; A. V. Golenkova; S. M. Kozlova; M. B. Arzhanik; Zh. A. Samoylenko; A. S. Boiko; A. V. Semke (Бюллетень сибирской медицины, 2019)
Objective. The authors tried to identify the typology, severity and overlap of neurocognitive deficits with positive/negative symptoms in patients with schizophrenia. Materials and methods. Fifty patients aged 22–55 years (25 women (50%) and 25 men (50%)) with schizophrenia diagnosed according to ICD-10 were examined. The average age was 38.0 ± 4.8 years, the average age of onset was 23 ± 3.2 years, the average disease duration was 15 ± 3.7 years. The patients were examined using battery tests to quantify their cognitive functions: Trail Making Test A&B; Stroop Color Word Interference Test; Verbal Fluency; Benton Visual Retention Test; 10 words learning; WAIS Digit Symbol Test; and WAIS Trail Making Test. The evaluation of cognitive deficits was carried out using z-scales. Association of neurocognitive deficits with other schizophrenia symptoms was also estimated using PANSS. The control group that was formed on the basis of the cognitive sphere parameters included 50 healthy volunteers. Statistical processing was carried out using the Mann–Whitney U test, k-means clustering, and the Kruskal-Wallis one-way analysis of variance. Results. The patients with schizophrenia and healthy individuals had significant differences in the second part of the Stroop Color Word Interference Test, both parts of the Verbal Fluency, average score of Benton Visual Retention Test, 10 words learning basedon 5 reiterations, WAIS Digit Symbol Test and WAIS Trail Making Test with p < 0.05; in the Trail Making Test B with p < 0.01. The cognitive sampling profile was determined and compared with the PANSS scores. The significant predominance (p < 0.05) of the symptoms across all scales was found with impaired attention, visual memory, performance function, and/or orientation/coordination, as opposed to the other manifestations of cognitive deficits. Conclusion. Neurocognitive deficits form syndromal overlaps with positive and negative schizophrenia syndromes, and the presence of attention, visual memory, performance and orientation / coordination disturbances is associated with the severity of schizophrenia in general.